2004
DOI: 10.1590/s0100-879x2004000500019
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and neonatal deaths in São Paulo, Brazil

Abstract: Air pollution has been associated with health effects on different age groups. The present study was designed to assess the impact of daily changes in air pollutants (NO 2 , SO 2 , CO, O 3 , and particle matter (PM 10 )) on total number of daily neonatal deaths (those that occur between the first and the 28th days of life) in São Paulo, from January 1998 to December 2000, since adverse outcomes such as neonatal deaths associated with air pollution in Brazil have not been evaluated before. Generalized additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 27 publications
5
39
0
16
Order By: Relevance
“…A remarkable aspect highlighted in this investigation is the fact that, during wet season (summer), contaminant concentrations and toxicities tended to be higher, which was not expected. Both literature and reports from the State Environmental Agency regularly inform that air pollution is worse during winter, that is, the dry season (Castanho and Artaxo 2001;CETESB 2009;Lin et al 2004;Orsini et al 1986;Sharovski et al 2004), and so, a worse condition in rainwater would be expected during dry season. Besides, it has been stated that better atmospheric conditions in wet seasons are a result of washing process produced by frequent rains (Castanho and Artaxo 2001;Lin et al 2004;Saldiva et al 1995), as demonstrated to other areas of the world (Singh et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable aspect highlighted in this investigation is the fact that, during wet season (summer), contaminant concentrations and toxicities tended to be higher, which was not expected. Both literature and reports from the State Environmental Agency regularly inform that air pollution is worse during winter, that is, the dry season (Castanho and Artaxo 2001;CETESB 2009;Lin et al 2004;Orsini et al 1986;Sharovski et al 2004), and so, a worse condition in rainwater would be expected during dry season. Besides, it has been stated that better atmospheric conditions in wet seasons are a result of washing process produced by frequent rains (Castanho and Artaxo 2001;Lin et al 2004;Saldiva et al 1995), as demonstrated to other areas of the world (Singh et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The metropolitan area of São Paulo (MASP) comprises one of the largest megalopolis of the world; with a population of over 19 million people (CETESB 2012) and a huge and increasing automotive fleet, this presents many environmental problems, including atmospheric pollution (Leal et al 2004;Lin et al 2004;Miraglia et al 2005;Santos et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(CONSTANTIN 1982;DÄSSLER & BORTITZ 1988;KRUPA & MANNING 1988;RODRIGUES et al, 1996;BRAY et al, 2000;LARCHER 2000;FERDINAND et al, 2000;ZHENG et al, 2002;entre outros (ROBBINS et al, 1992;PEREIRA et al, 1998;MARTINS et al, 2002;BAKONY et al, 2004;LIN, et al, 2004;CANÇADO, et al, 2006 (SALDIVA et al, 1995;RIBEIRO et al, 2003;DAUMAS, et al,2004).…”
Section: Dissertação De Mestradounclassified
“…Essa ocorrência se intensifica no inverno através do aumento de inversões térmicas, que bloqueiam a dispersão de poluentes atmosféricos primários, provocando episódios agudos de poluição. No Brasil, alguns estudos demonstram o retardo do crescimento intrauterino, menor peso ao nascer e maior mortalidade intrauterina e neonatal segundo PEREIRA et al (1998);LIN et al (2004) e MEDEIROS et al (2005.…”
Section: Poluição E Saúdeunclassified